2022
DOI: 10.1111/epi.17442
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic scores in status epilepticus: A systematic review and meta‐analysis

Abstract: The performance of prognostic scores of status epilepticus (SE) has been reported in very heterogeneous cohorts. We aimed to provide a summary of the available evidence on their respective performance. PubMed and EMBASE were searched for relevant articles. Studies were reviewed for eligibility for meta‐analysis of the area under the receiver‐operating characteristic curve (AUC) and for meta‐analysis of sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) in predicting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Yet, similar to our results, the performance of these scores (aside from describing a cohort) exhibits significant divergence among various cohorts. Yuan et al 11 performed a meta‐analysis providing pooled AUCs for STESS (.741, range = .574–.864), EMSE (.765, range = .636–.860), and END‐IT (.783, range = .659–.843) when predicting in‐hospital mortality. When considering the development of scores, however, the original study generally outperforms its competitors and validation studies when considering its own dataset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, similar to our results, the performance of these scores (aside from describing a cohort) exhibits significant divergence among various cohorts. Yuan et al 11 performed a meta‐analysis providing pooled AUCs for STESS (.741, range = .574–.864), EMSE (.765, range = .636–.860), and END‐IT (.783, range = .659–.843) when predicting in‐hospital mortality. When considering the development of scores, however, the original study generally outperforms its competitors and validation studies when considering its own dataset.…”
Section: Discussionmentioning
confidence: 99%
“…These include Status Epilepticus Severity Score (STESS), 7,8 Epidemiology‐Based Mortality Score in Status Epilepticus (EMSE), 9 and END‐IT (including the predictors encephalitis, NCSE, diazepam resistance, imaging features, and tracheal intubation, which form the acronym) 10 . STESS, EMSE, and to a lesser degree END‐IT (due to its more recent development) have been validated for various patient cohorts 11 . These include descriptions in different countries, 12–14 different age groups, 15,16 and some intensive care unit populations 17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently available clinical scores lack accuracy. 7 In Bonduelle et al, the presence of PMA was not associated with higher status epilepticus severity scores, the most frequently used score, but it was associated with mortality, even when accounting for age and etiology, two components of most SE severity scores. In Cornwall et al, the association of PMA with mortality was significant, even when adjusting for the epidemiology-based mortality in SE score.…”
Section: Commentarymentioning
confidence: 94%
“…13 However, a recent meta-analysis assessing prognostic scores developed for use in SE (including EMSE and STESS) showed that while all scores had high negative predictive values (0.89-0.95), their positive predictive values were quite low (0.2-0.35) indicating that the likelihood of correctly identifying survival following SE is high, but ability to accurately detect mortality is low. 14 Therefore, caution should be used when applying these scores.…”
Section: Eeg Features Of Prognostication In the Acute Critically Ill ...mentioning
confidence: 99%